Impact of Ethnomathematics-Based Learning on Mbojo Students’ Mathematical Communication Skills in Indonesia - Mariamah Mariamah; Nanang Diana; Adi Apriadi Adiansha; Muslim Muslim; Khusnul Khatimah (Universitas Pendidikan Mandalika, 2026)
Mathematical communication skills are essential for enabling students to express mathematical ideas, use representations, and explain reasoning clearly. However, elementary students often experience difficulties in using mathematical symbols, interpreting visual representations, and presenting problem-solving steps systematically. This study examined students’ mathematical communication skills after the implementation of ethnomathematics-based learning using Mbojo cultural contexts. A quasi-experimental method with a one-group posttest-only design was employed. The participants were 15 fourth-grade students selected through total sampling. Data were collected using a mathematical communication skills test and analyzed using a one-sample t-test with a benchmark score of 70, based on the Minimum Mastery Criteria. The results showed that students’ mean score was 73.87, which was significantly higher than the benchmark, t(14) = 2.822, p = .015. These findings indicate that ethnomathematics-based learning using Mbojo cultural contexts can support students’ mathematical communication skills. However, due to the absence of a pretest and control group, the findings should be interpreted as evidence of students’ achievement above the benchmark rather than strong causal evidence.